2019
DOI: 10.1371/journal.pone.0217126
|View full text |Cite
|
Sign up to set email alerts
|

Disrespect and abuse during childbirth in Western Ethiopia: Should women continue to tolerate?

Abstract: Background Healthcare coverage in Ethiopia has improved dramatically in recent decades. However, facility-based delivery remains persistently low, while maternal mortality remains high. This paper presents the prevalence and associated factors of disrespect and abuse (D&A) during childbirth in public health facilities of western Oromia, Ethiopia. Method A facility-based cross-sectional study was conducted among 612 women from February 2017 to May 2017. Exit interview wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
7
39
3
Order By: Relevance
“…In this study, three out of four (75.1%) women reported to be subjected to at least one form of OV. The prevalence of OV in the current study is consistent with that of the previous studies done in Ethiopia such as Addis Ababa—78% [19] and Western Ethiopia—74.8% [20].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, three out of four (75.1%) women reported to be subjected to at least one form of OV. The prevalence of OV in the current study is consistent with that of the previous studies done in Ethiopia such as Addis Ababa—78% [19] and Western Ethiopia—74.8% [20].…”
Section: Discussionsupporting
confidence: 91%
“…But the result of this study is also higher than a study conducted in Arbaminch which revealed the overall prevalence of respectful care to be only 1.1% 8 and Addis Ababa (21.4%), Western Ethiopia (25.2%), 6 , 10 Tanzania (36%), 14 and Gujrat, Pakistan. 7 , 15 This could be due to the differences in study settings, methods, and tools.…”
Section: Discussioncontrasting
confidence: 83%
“…1 Previous studies conducted in Ethiopia showed as there is disrespect and abusing during delivery For instance, studies in Arbaminch, Bale zone, West Ethiopia, and Bahir Dar stated that the proportions of disrespectful maternity care were 98.9%, 37.5%, 74.8%, and 57% respectively. [8][9][10][11] However, the results of these previous studies were not consistent and limited in number in the context of Ethiopia. Hence, this study aimed to assess respectful maternity care and associated factors among women who attended delivery services in Northwest Amhara, Referral Hospitals, Ethiopia.…”
Section: Introductionmentioning
confidence: 73%
“…This theme is linked to the poor quality of care provided as well as distrust in the competence of providers. Previous studies in Ethiopia [ 42 , 43 ] and elsewhere [ 44 , 45 ] demonstrate that women experienced various forms of mistreatment in health facilities. The Ethiopian health system recognizes compassionate, patient-centered care as a priority in the efforts to improve quality and equity in service delivery, as noted in its Health Sector Transformation Plan [ 32 ].…”
Section: Discussionmentioning
confidence: 99%